EXPLORATION OF COLLAGEN AND GELATIN HYDROLYSATES FROM ANIMAL WASTE AS FUNCTIONAL FEED INGREDIENTS: A REVIEW - Trisusanti Trisusanti; Irma; Ana Fitria; Desima Natalia Harianja; M. Dzikri Hudiatma; Ryzal Satri Aditama; Fikya Juanda (Journal of Animal Research and Applied Science, 2026)
The increasing volume of collagen and gelatin rich by-product waste from the livestock and fishery industries triggers environmental pollution if not managed optimally. This article aims to review the potential utilization of collagen and gelatin hydrolysates from animal waste as functional feed ingredients that support the sustainability of the livestock industry. The review was conducted by searching and analyzing various research findings on animal waste sources, methods of producing bioactive peptides, biological activities, and their effectiveness in animal feed. The application of bioactive peptides in feed has been shown to be able to improve growth performance, feed conversion efficiency, gastrointestinal health, carcass quality, and the resistance of livestock to oxidative stress and disease. In addition to increasing livestock productivity, the utilization of animal waste as a source of bioactive peptides also supports the concept of a circular economy and sustainable waste management. However, its application still faces technical and biological challenges, such as the risk of zoonotic diseases, the halal status of raw materials, quality variability, and the vulnerability of peptides to degradation at high temperatures during feed manufacturing processes such as pelletization. As a solution, the utilization of this waste requires standardization of the extraction process, encapsulation technology to maintain peptide stability, and the implementation of a strict quality assurance system. This innovative approach not only provides a competitively valued alternative protein source but also supports the implementation of circular economy principles and zero-residue waste management.